Preparation of MnBi LTP magnets by direct sintering
Through the two-stage sintering method, the problem of difficulty in preparing MnBi alloys in the prior art is solved, and the preparation of high yield and high purity MnBi LTP magnets is achieved, which simplifies the production process and reduces costs.
Patent Information
- Application Number
- CN201810630927.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-06-20
- Filing Date
- 2018-06-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2038-06-19
AI Technical Summary
The prior art is difficult to efficiently prepare low-temperature phase MnBi alloys with high purity and high yields, and the traditional methods are complex and expensive, making it difficult to expand into mass production.
Using a two-stage sintering method, first sintering Mn and Bi powders at higher temperatures to form a predetermined period of time, and then sintering continues at lower temperatures. By increasing the phase change driving force and shortening the energy barrier, the nucleation and growth of MnBi LTP are promoted. .
The yield and volume ratio of MnBi LTP magnets is significantly improved, the production cost is reduced, and a cost-effective and scalable mass production method is provided.
Smart Images

Figure CN109102978B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to low temperature phase (LTP) manganese bismuth (MnBi) permanent magnets and methods of manufacturing LTP MnBi permanent magnets. Background Art
[0002] MnBi alloys have been identified as suitable replacements for rare earth permanent magnets due to their unique properties, such as high coercivity that increases with temperature and, therefore, high stability when demagnetizing the magnetic field at high temperatures. This is particularly important for use in traction electric motors, which typically operate at high temperatures. Obtaining magnetic low temperature phase (LTP) MnBi alloys with high purity and high yield of LTP remains difficult, partly due to the peritectic reaction between manganese (Mn) and bismuth (Bi) and due to the low phase transformation temperature required for nucleation and growth of the MnBi LTP. Summary of the invention
[0003] According to an embodiment, a method is disclosed, the method comprising: sintering a Mn and Bi powder compact at a first temperature for a first predetermined period of time based on a first temperature; sintering the compact at a second temperature less than the first temperature for a second predetermined period of time, wherein the second predetermined period of time is greater than the first predetermined period of time. The step of sintering the first predetermined period of time at the first temperature generates a predetermined MnBi LTP transformation driving force to reduce the formation energy barrier for transformation to MnBi LTP. The step of sintering the compact at the second temperature for a second predetermined period of time forms a magnet containing MnBi LTP.
[0004] According to one or more embodiments, the first predetermined period may be between about 1 minute and 120 minutes. The first temperature may be between about 360°C and 900°C. The second predetermined period may be between about 1 hour and 48 hours. The second temperature may be about 260°C to 450°C. In some embodiments, the method may further include: mixing and pressing Mn and Bi powders to form a compact. The X-ray diffraction peak intensity of the MnBi LTP may be at least twice the X-ray diffraction peak intensity of the Bi peak in the magnet. In some embodiments, the method may further include: crushing and grinding the magnet to form a powder containing MnBi LTP; pressing the powder containing MnBi LTP into a compact containing LTP; repeating the sintering step. In yet another embodiment, the method may further include: crushing and grinding the magnet to form a powder containing MnBi LTP; pressing the powder containing MnBi LTP into a compact containing LTP; repeating the step of sintering the second predetermined period at a second temperature.
[0005] According to an embodiment, a high-yield MnBi LTP magnet formed by the above-described method is disclosed.
[0006] According to an embodiment, a method for manufacturing a high-yield MnBi LTP magnet is disclosed, comprising: sintering a Mn and Bi powder compact at a first temperature for a first period of time; sintering at a second temperature less than the first temperature for a second period of time, so that the X-ray diffraction peak intensity of the MnBi LTP is at least twice the X-ray diffraction peak intensity of Bi, wherein the second period of time is greater than the first period of time. The step of sintering the compact at the first temperature for the first period of time provides a phase change driving force for the nucleation and growth of the MnBi LTP.
[0007] According to one or more embodiments, the method may further include: crushing and grinding the compact to form a powder containing MnBiLTP. The method may further include: pressing the powder containing MnBi LTP into a compact containing LTP; repeating two sintering steps, or repeating the step of sintering the second period at a second temperature. The grinding step may include low-energy ball milling, cryogenic milling, or jet milling. In some embodiments, the first temperature may be between about 360°C and 900°C. The first period may be between about 1 minute and 120 minutes. The second temperature may be between about 260°C and 450°C. The second period may be between about 1 hour and 48 hours. According to some embodiments, the Mn and Bi powder compact may be a mixture of about 0.8:1 to 1:0.8 atomic ratios of ground Mn powder and ground Bi powder. In yet another embodiment, the first temperature may be about 660°C, the first period may be between about 40 minutes and 80 minutes, and the second temperature may be about 340°C, and the second period may be about 24 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is a graph showing the effect of nucleation on the total free energy of an alloy system.
[0009] Figure 2 is a graph showing X-ray diffraction patterns of Mn-Bi sintered at 360°C and below 360°C for 24 hours.
[0010] Figure 3 is a schematic diagram of a sintering method according to an embodiment.
[0011] Figure 4 is a graph showing X-ray diffraction patterns of Mn—Bi sintered at 560° C. for different periods of time (as a first stage before low temperature sintering) according to an embodiment.
[0012] Figure 5 is a graph showing X-ray diffraction patterns of Mn—Bi samples sintered for different periods of time, 40 minutes (top) and 80 minutes (bottom), according to an embodiment. DETAILED DESCRIPTION
[0013] As required, detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are merely examples of the present invention, which may be implemented in various and alternative forms. The drawings are not necessarily drawn to scale; some features may be exaggerated or minimized to show details of particular components. Therefore, the specific structural and functional details disclosed herein should not be interpreted as limiting, but merely as a representative basis for teaching those skilled in the art to use the present invention in various ways.
[0014] Unless expressly indicated otherwise, all numerical values indicating dimensions or material properties in the present embodiments are to be understood as being modified by the word "about" in describing the broadest scope of the present disclosure.
[0015] The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein, and general grammatical variations of the abbreviation specified in the initial definition apply mutatis mutandis. Unless expressly specified to the contrary, measurements of properties are determined by the same techniques as previously or later referenced for the same property.
[0016] Combinations, embodiments and methods known to the inventors of the present invention are described in detail. However, it should be understood that the disclosed embodiments are merely examples of the present invention that can be implemented in various and alternative forms. Therefore, the specific details disclosed herein should not be interpreted as limiting, but only as a representative basis for teaching those skilled in the art to use the present invention in various ways.
[0017] Description of a group or class of materials, in connection with one or more embodiments of the invention, as suitable for a given purpose implies that mixtures of any two or more of the components of the group or class are suitable. Descriptions of components in chemical terms refer to the components when added to any combination specified in the specification, and do not necessarily preclude chemical interactions between the components of the mixture after mixing. The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein, and general grammatical variations of the abbreviation specified in the initial definition apply mutatis mutandis. Unless expressly specified to the contrary, measurements of properties are determined by the same techniques as those mentioned previously or later for the same property.
[0018] Permanent magnet is a material that produces its own permanent magnetic field. Permanent magnets are used in various applications. For example, in green energy applications such as electric vehicles or wind turbines, neodymium-iron-boron (Nd-Fe-B) magnets are often used. For these applications, permanent magnets must be able to maintain magnetism at high temperatures. Permanent magnet materials have been widely used in motors for various applications (including industrial fans, blowers and pumps, machine tools, household appliances, power tools, electric vehicles and disk drives). For most applications (especially high-end applications, for example, in electric vehicles), high-performance rare earth permanent magnet materials are required.
[0019] Such permanent magnets are usually produced using rare earth elements that can produce high anisotropy fields and have therefore become the basic components of high coercivity permanent magnets. In addition, heavy rare earth metals are used to increase the coercivity in order to stabilize the permanent magnets for high temperature operation. Rare earth materials are expensive (particularly, heavy rare earth materials are much more expensive than light rare earth materials), and the supply of these materials is at risk. A lot of effort has been put into finding permanent magnet materials without rare earths.
[0020] Among various types of rare earth-free permanent magnets, MnBi magnets are one of the most promising materials for high-temperature permanent magnet applications. The low temperature phase (LTP) of MnBi alloy has a 6 Jm -3 The ferromagnetic LTP of MnBi alloy has unique characteristics. Specifically, the coercivity of the LTP of MnBi alloy has a large positive temperature coefficient, which means that the coercivity of the magnet made of LTP MnBi increases with increasing temperature. This unique property makes MnBi magnet an excellent candidate for high temperature applications to replace rare earth-based permanent magnets that usually contain more expensive heavy rare earth elements for high temperature applications, or at least reduce the dependence on heavy rare earth elements.
[0021] However, the saturation magnetization of MnBi alloys at 300K is relatively low, about 0.9T. MnBi alloys are usually composed of other phases such as non-magnetic Mn and Bi (the other phases are phases that do not contribute to the magnetic properties). MnBi magnets can be used directly as permanent magnets or nanocomposite magnets for exchange coupling. A prerequisite for all applications is that the magnet has high-purity MnBi LTP. However, obtaining a high volume ratio of MnBi LTP in MnBi alloys has become a problem.
[0022] MnBi LTP is usually made from a Mn-Bi alloy, and the phase transition from separate Mn and Bi phases to MnBi LTP occurs below 360°C, which is very low for the atoms to overcome the energy barrier for the phase transition. Due to the low temperature and low energy atoms, the phase transition is usually very slow, which leads to complex and expensive methods for making magnets. These methods include methods such as melt spinning, ball milling, and arc melting followed by annealing. Using processes like these is usually very expensive, which makes it difficult to scale up for mass production.
[0023] Although conventional metallurgical methods such as arc melting and sintering may be economically feasible, the MnBi alloys prepared by these methods contain relatively high volumes of non-magnetic Mn and Bi phases because the reaction between Mn and Bi is a peritectic reaction, which causes the solid phase and the liquid phase to form another solid phase at a certain temperature. During solidification, Mn first solidifies into large particles from the MnBi liquid. Heat treatment or annealing is performed at low temperatures to obtain MnBi LTP. However, the volume ratio of MnBi LTP is limited by the nature of the peritectic reaction and the low reaction temperature. The reaction between Mn and Bi is slow, and pure MnBi LTP cannot be obtained even after various heat treatments, and the complex and long heat treatment significantly increases the cost.
[0024] Figure 1 The effect of nucleation on the total free energy of the alloy system based on the atomic number (N) is shown. As mentioned above, although direct sintering of Mn and Bi powders has been attempted, the low phase transformation temperature of 360°C results in extremely long annealing times. At such temperatures, not only is the nucleation rate of the MnBi LTP low, but the formation of the LTP also results in the formation of a new interface between the LTP and the initial alloy due to peritectic reactions. Although the formation of the LTP reduces the total energy of the mixture, the energy increase due to the formation of the new interface cannot be offset when the MnBi LTP is small, such as Figure 1 This slows down the phase transition and even causes it to proceed in the opposite direction, causing LTP to decompose into Mn and Bi.
[0025] The yield is very low by direct sintering at different temperatures below the low phase transition temperature of 360° C. The yield improvement by extending the annealing time is limited and several days or even weeks of annealing are required to obtain a significant yield improvement. Figure 2 The X-ray diffraction patterns of Mn-Bi directly sintered at different temperatures below 360°C for 24 hours are shown. Figure 2 In the graph, the peak of MnBi LTP with the highest relative intensity (as marked with solid diamonds) is even barely visible, thus indicating that MnBi LTP is of low yield.
[0026] According to one or more embodiments, a method for preparing MnBi LTP magnets by two-stage direct sintering is disclosed. The advantage of the process described herein lies in the ability to improve the LTP yield of MnBi LTP magnets by using a powder metallurgy method of directly sintering Mn and Bi powders in two stages. The disclosed method overcomes the energy barrier to result in higher yield without segregation problems in the resulting magnets, thereby providing high-yield MnBi LTP magnets.
[0027] The method uses powders of separate components Mn and Bi, wherein the powders of components Mn and Bi are mixed and sintered. As long as the powders are evenly mixed, the processing efficiency is less affected by the volume of the alloy, which makes the method easier to expand to mass production. A mixer, a cryogenic grinder, or a low-energy ball mill is used to mix the powders of Mn and Bi. Mn powder and Bi powder are mixed in an atomic ratio of about 0.8:1 to 1:0.8. In an embodiment, Mn powder and Bi powder are mixed in an atomic ratio of about 1:1. The mixed powder is then pressed into a compact, such as a green compact. The compact is then sintered in an inert gas atmosphere such as argon, nitrogen, or helium. The atmosphere can also be a mixture of these inert gases or a mixture of an inert gas and hydrogen (because hydrogen prevents oxide formation).
[0028] Figure 3 A schematic diagram of a sintering step according to one or more embodiments is shown. The sintering of the green compact is a two-stage process, wherein first for the first stage, the green compact is sintered at a first temperature for a first predetermined period of time, and then for the second stage, the green compact is sintered at a second temperature for a second predetermined period of time. The first predetermined period of time and the second predetermined period of time are based on the first temperature and the second temperature used for sintering. Figure 3 As shown, the temperature in the furnace for sintering is increased to a first temperature T1 for a first period t1. Then, the temperature is reduced to a second temperature T2 for a second period t2, which is longer than the first period t1. The first temperature T1 may be between about 360°C and 900°C. In some embodiments, the first temperature T1 may be between about 360°C and 800°C. The first period t1 (i.e., the shorter period) may be between about 1 minute and 120 minutes. In some embodiments, the first period t1 may be between about 10 minutes and 120 minutes. The second temperature T2 may be between about 260°C and 460°C. In some embodiments, the second temperature T2 may be between about 260°C and 360°C. The second period t2 (i.e., the longer period) may be between about 1 hour and 48 hours. In some embodiments, the second period t2 may be between about 1 hour and 24 hours. In other embodiments, the second period t2 may be between about 4 hours and 24 hours. The high cooling rate between the two stages is preferably to promote the formation of MnBi LTP.
[0029] By adding a first sintering stage at a higher temperature, the interphase diffusion between Mn and Bi can be promoted, and the formation barrier for the growth of MnBi LTP grains is reduced. The driving force for the phase change is increased to a predetermined range to reduce the formation barrier. A predetermined MnBi LTP transformation driving force is established based on the selected first stage temperature and time period to reduce the formation barrier, thereby more conducive to the transformation to MnBi LTP. Sintering in two stages improves the growth of MnBi LTP atomic clusters. Once the number of atoms exceeds N* (such as Figure 1 As depicted), the growth of clusters will be more active and smooth, and thus, the phase transition will be accelerated. Therefore, increasing the temperature T1 or the length of the first period t1 relative to the second stage can increase the volume ratio of MnBi LTP.
[0030] Figure 4 X-ray diffraction patterns of MnBi for exemplary compacts sintered at 560°C for different periods of time are shown. The exemplary compact was sintered at 560°C (T1) for 10 minutes (t1), and then the temperature was reduced to 340°C (T2) for 24 hours (t2). Figure 4 With Figure 2 Compared to direct sintering at 340 °C for 24 hours for a single stage, the results show a significant increase in volume ratio by using a two-stage approach. Figure 4 In the X-ray diffraction pattern, the peak of MnBi LTP is obvious, and the intensity of the peak gradually increases with time at 560°C. The increase in peak intensity indicates that the volume ratio of MnBi LTP increases with time, although there are smaller peaks of other components.
[0031] In some embodiments, the first time period t1 may be optimized to provide the strongest predetermined phase change driving force to overcome the energy barrier, so that the phase change during the second stage is faster. Figure 5 X-ray diffraction patterns are shown for a MnBi sample sintered at 660°C for 40 minutes (top) and 80 minutes (bottom) in a first stage and then at 340°C for 24 hours in a second stage. Figure 5 It is shown that for this first temperature T1, 80 minutes is sufficient to produce a higher volume fraction of MnBi LTP, as shown by the characteristic peak of MnBi LTP, which is much stronger than the remaining Bi (next to and to the left of the MnBi LTP peak). Therefore, since the first stage provides the driving force for the phase change and can be optimized for the selected temperature, high cost and segregation can be avoided by a two-stage process.
[0032] By increasing T1, the X-ray diffraction peak intensity of MnBi can be gradually increased, but when the temperature is too high (above 900°C), segregation occurs between the phases and the distance between the Mn and Bi atoms becomes longer, which makes it difficult for the phase transition to continue. The time period t1 of the first stage is very important for the formation of MnBi LTP. Generally, a longer time is better for the formation of MnBi LTP, but for the corresponding temperature, segregation may also occur beyond the optimal time period t1. In other embodiments, the first temperature T1 can be higher and combined with a longer second time period t2 compared to the Bi peak, which can result in a higher peak intensity of the MnBi LTP.
[0033] In some embodiments, the method may further include repeating the sintering process. Before repeated sintering, the sintered green compact (containing MnBi LTP) may be crushed and cryogenically ground, low-energy ball milled or jet milled into a fine powder (containing a powder of MnBi LTP) and pressed into a green compact containing LTP to repeat the sintering process, thereby further increasing the weight ratio of MnBi LTP. In some embodiments, two sintering stages are repeated. In one or more embodiments, only the second sintering stage is repeated. In other embodiments, a jet mill may be used to separate the ground powder to separate the MnBi LTP from the individual phases, and the remaining Mn and Bi powders may be pressed into a green compact and sintered again through a two-stage process to obtain a higher overall yield.
[0034] A method for preparing MnBi LTP magnets by two-stage direct sintering is disclosed. The two-stage sintering method provides a first stage that increases the driving force for phase transformation, so that a higher yield of MnBi LTP is grown in the second stage. The two-stage process provides an effective method for increasing the yield of MnBi LTP by greatly reducing the time required to obtain high-yield MnBi LTP, while still providing a technically and economically feasible method for mass production.
[0035] Although exemplary embodiments are described above, it is not intended that these embodiments describe all possible forms of the present invention. More specifically, the words used in the specification are descriptive rather than restrictive, and it should be understood that various changes may be made without departing from the spirit and scope of the present invention. In addition, the features of multiple implemented embodiments may be combined to form further embodiments of the present invention.
Claims
1. A method comprising: sintering the Mn and Bi powder compact at the first temperature for a first predetermined period of time based on the first temperature to generate a predetermined driving force for MnBiLTP transformation, thereby reducing a formation energy barrier for transformation to MnBi LTP; sintering the compact at a second temperature less than the first temperature for a second predetermined period of time to form a magnet comprising MnBi LTP, wherein the second predetermined period of time is greater than the first predetermined period of time, Wherein, the first temperature is between 560° C. and 660° C., the first predetermined period is between 40 minutes and 80 minutes, the second temperature is between 260° C. and 340° C., and the second predetermined period is between 4 hours and 24 hours.
2. The method according to claim 1, further comprising: Mn and Bi powders are mixed and pressed to form the green compact.
3. The method according to claim 1, further comprising: crushing and grinding the magnet to form a powder containing MnBiLTP; pressing the powder containing MnBi LTP into a compact containing LTP; repeating the steps of sintering at the first temperature for the first predetermined period of time and sintering at the second temperature for the second predetermined period of time.
4. The method according to claim 1, further comprising: The steps of crushing and grinding the magnet to form a powder comprising MnBiLTP; pressing the powder comprising MnBi LTP into a compact comprising LTP; and repeating sintering at the second temperature for the second predetermined period of time.
5. The method according to claim 3 or 4, wherein: The grinding step includes low energy ball milling, cryogenic grinding or jet milling.
6. The method according to claim 1, wherein: The Mn and Bi powder compact is a mixture of ground Mn powder and ground Bi powder in an atomic ratio of 0.8:1 to 1:0.
8.
7. The method according to claim 1, wherein: The first temperature is 660° C., and the second temperature is 340° C., and the second predetermined period is 24 hours.
8. A method for producing a high-yield MnBi LTP magnet, comprising: sintering the Mn and Bi powder compact at a first temperature for a first period of time to provide a phase transformation driving force for nucleation and growth of the MnBi LTP; sintering at a second temperature less than the first temperature for a second period of time so that the X-ray peak intensity of the MnBi LTP is at least twice the X-ray peak intensity of Bi, wherein the second period of time is greater than the first period of time, The first temperature is between 560° C. and 660° C., the first period is between 40 minutes and 80 minutes, the second temperature is between 260° C. and 340° C., and the second period is between 4 hours and 24 hours.
9. The method according to claim 8, further comprising: The green compact was crushed and ground to form a powder comprising MnBiLTP.
10. The method according to claim 9, further comprising: The powder containing MnBi LTP is pressed into a compact containing LTP; and the step of sintering at the first temperature for the first period of time and the step of sintering at the second temperature for the second period of time are repeated, or the step of sintering at the second temperature for the second period of time is repeated.
11. The method according to claim 9, wherein: The grinding step includes low energy ball milling, cryogenic grinding or jet milling.
12. The method according to claim 8, wherein: The Mn and Bi powder compact is a mixture of ground Mn powder and ground Bi powder in an atomic ratio of 0.8:1 to 1:0.
8.
13. The method according to claim 8, wherein: The first temperature is 660° C., and the second temperature is 340° C., and the second period of time is 24 hours.
Citation Information
Patent Citations
Method for preparing high-purity MnBi alloy
CN105671346A
Preparation method of rare earth doped high-coercivity manganese-bismuth alloy magnetic powder
CN105689726A
Anisotropic complex sintered magnet comprising MnBi, and method of preparing the same and product comprising the same
CN105702444A
Anisotropic complex sintered magnet containing manganese bismuth and pressureless sintering method therefor
CN106537525A
Boron doped manganese antimonide as a useful permanent magnet material
US20150110662A1
